Testing and numerical modelling of S960 ultra-high strength steel angle and channel section stub columns. (1st February 2020) - Wang, Fangying; Zhao, Ou; Young, Ben
Highlights: Stub column tests were conducted on press-braked S960 ultra-high strength steel angle and channel sections. Numerical models were developed and validated against test results, and then used to perform parametric studies. The existing codified design rules were assessed against the test and numerical results, indicting inaccuracy. Revised design rules were proposed and shown to yield improved design accuracy. Abstract: A comprehensive experimental and numerical study of the cross-sectional compressive behaviour and resistances of press-braked S960 ultra-high strength steel (UHSS) angle and channel section stub columns is reported in this paper. The experimental study was carried out on four equal-leg angle sections and eight plain channel sections, and comprised material testing, initial local geometric imperfection measurements and 18 stub column tests. The experimental setups, procedures and key observations were fully presented. The experimental study was then supplemented by a finite element (FE) simulation programme, in which FE models were firstly developed to replicate the test structural responses and subsequently used to generate further numerical data over a wide variety of cross-section sizes. It is worth noting that the current international standards established in Europe, America and Australia/New Zealand only cover the design of structural members with material grades up to S700, and thus the examined S960 UHSS angle and channel section stub columns are out of the scope of the existing design standards. In this study, the experimentally and numerically acquired data was adopted to assess the applicability of the codified provisions and formulations to the design of S960 UHSS angle and channel section stub columns. The assessment results generally indicated that the current European code leads to overall consistent and accurate predictions of cross-section compression resistances, but with many overestimated predicted resistances for S960 UHSS channel section stub columns, while the American and Australian/New Zealand standards yield unduly scattered design cross-section compression resistances, with unsafe and overly conservative predicted resistances respectively for S960 UHSS channel section stub columns and slender angle section stub columns. Revised codified design rules were also proposed, and shown to yield safe, accurate and consistent design cross-section compression resistances for S960 UHSS angle and channel section stub columns.